Implementasi Pemungutan Pajak Bumi Dan Bangunan Perdesaan Dan Perkotaan Pada Kecamatan Medan Tembung Kota Medan - Ricky Sofian Hasibuan; Badaruddin Badaruddin; Muryanto Amin (Universitas Medan Area, 2021)
This research raises the phenomenon of Land and Building Tax Collection in Rural and Urban Areas in Medan Tembung District. In this study, researchers used implementation theory by applying the George C Edward III model implementation. This theory uses 4 variables, namely communication, resources, disposition and bureaucratic structure. If one of these variables is not met, obstacles will be found that cause the PBB-P2 collection process in Medan Tembung District to be ineffective. This study uses a qualitative approach with data observation techniques, interviews, and documentation. Meanwhile, data analysis techniques use data reduction, data presentation, and data collection. The results showed that the implementation of PBB-P2 collection policy in Medan was not yet effective because it did not fulfill all the factors and variables determined by George C. Edward III. Policy implementers are only able to fulfill 1 factor, namely the variable of bureaucratic structure consisting of SOPs and fragmentation only so that it has an impact on the results of realization that have not increased and have actually decreased over the last 3 years. Another obstacle is the low level of public awareness and the unfulfilled variable implementation of the George C Edward III model, such as in the communication factor, there is transmission, clarity, disposition and resources which have not been properly resolved by policy implementers.